Scaphotrapeziotrapezoid Arthrodesis: A 10-Year Follow-up Study of Complications in 58 Wrists. (September 2022) - Rogers, Miranda J.; Lu, Chao-Chin; Stephens, Andrew R.; Garcia, Brittany N.; Chen, Wei; Sauer, Brian C.; Tyser, Andrew
Background: Scaphotrapeziotrapezoid (STT) arthrodesis is a procedure used for specific degenerative arthritis and instability patterns of the wrist. This study evaluates nonunion rate and risk factors for reoperation after STT arthrodesis in the Veterans Affairs Department patient population. The purpose of our study was to assess the long-term nonunion rate following STT arthrodesis and to identify factors associated with reoperation. Methods: The national Veterans Health Administration Corporate Data Warehouse and Current Procedural Terminology codes identified STT arthrodesis procedures from 1995 to 2016. Frequencies of total wrist arthrodesis (TWA) and secondary operations were determined. Univariate analyses provided odds ratios for risk factors associated with complications. Results: Fifty-eight STT arthrodeses were performed in 54 patients with a mean follow-up of 120 months. Kirschner wires (K-wires) were the most common fixation method (69%). Six wrists (10%) required secondary procedures: 5 TWAs and 1 revision STT arthrodesis. Four patients underwent additional procedures for nonunion (7%). Twenty-four patients required K-wire removal, 8 (14%) of these in the operating room, which were not included in regression analysis. Every increase in 1 year of age resulted in a 15% decrease in likelihood of reoperation (95% confidence interval: 0.77-0.93; P < .0001). Opioid use within 90 days before surgery ( P = 1.00), positive smoking history ( P = 1.00), race ( P = .30), comorbidity count ( P = .25), and body mass index ( P = .19) were not associated with increased risk of reoperation. Conclusions: At a mean follow-up of 10 years, patients undergoing STT arthrodesis have a 10% risk of reoperation, and this risk decreases with older patient age. There was a symptomatic nonunion rate of 7%, similar to prior published rates. Patient demographics, comorbidity, smoking history, and opioid use did not appear to increase risk of reoperation.